Dare to Speak 2.0 / Norhafizah Abdul Halil, Isma Noornisa Ismail and Anis Shaari - Abdul Halil, Norhafizah; Ismail, Isma Noornisa; Shaari, Anis (Academy of Language Studies, 2024)
The Academy of Language Studies (ALS) of UiTM Penang Branch, in collaboration with the Resource Center of SK Permatang Bertam, the Highly Immersive Program (HIP) Unit, and the English Language Committee of SK Permatang Bertam in Kepala Batas,Penang, organised the Dare to Speak 2.0 Public Speaking Program on October 28, 2023. Supported by 28 lecturers from the Academy of Language Studies, this community service program involved 88 students from Level 2 (Year 4 to Year 6) of Sekolah Kebangsaan Permatang Bertam in Kepala Batas and surrounding schools. The program commenced with an opening ceremony, including an address by the Program Director, Ms. Norhafizah AbdulHalil, followed by an inaugural speech by the Headmaster of SK Permatang Bertam, Mr. Hj Roslan Othman. Subsequently, thee vent proceeded with a certificate and souvenir presentation session to the school and participating students, followed by a photography session. After the opening ceremony, students were divided into 8 groups for group activity sessions. Each group was facilitated by two instructors, consisting of lecturers from APB. The modules provided were based on public speaking activities, including exercises such as Show and Tell and the Story telling Challenge. These activities aligned with the program's objective of helping students master the fundamentals of public speaking in English. Other than strengthening the bonds and rapport between APB staff and the local residents, this program also managed to cultivate a caring and sincere attitude among APB staff through pure efforts such as donations and knowledge-sharing. Thus, the program indeed fostered a spirit of cooperation, mutual assistance, tolerance, and teamwork among APB staff.